College Algebra - Abramson, Jay; Open Textbook Library (Open Textbook Library, 2015)
College Algebra provides a comprehensive and multi-layered exploration of algebraic principles. The text is suitable for a typical introductory Algebra course, and was developed to be used flexibly. The modular approach and the richness of content ensures that the book meets the needs of a variety of programs.College Algebraguides and supports students with differing levels of preparation and experience with mathematics. Ideas are presented as clearly as possible, and progress to more complex understandings with considerable reinforcement along the way. A wealth of examples - usually several dozen per chapter - offer detailed, conceptual explanations, in order to build in students a strong, cumulative foundation in the material before asking them to apply what they've learned. OpenStax College has compiled many resources for faculty and students, from faculty-only content to interactive homework and study guides.
1 Prerequisites -- 2 Equations and Inequalities -- 3 Functions -- 4 Linear Functions -- 5 Polynomial and Rational Functions -- 6 Exponential and Logarithmic Functions -- 7 Systems of Equations and Inequalities -- 8 Analytic Geometry -- 9 Sequences, Probability, and Counting Theory
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks